Antecedents in influence of Universiti Malaysia Kelantan staff job performance - Mohd Hafizuddin Hiew Abdullah @ Hiew Yeap Seng; Al-Arabi Mohamed; Muhamad Nasyat Muhamad Nasir; Muhammad Ridzuan Che Hassan; Razli Che Razak (The International Institute of Social and Economic Sciences, 2016)
Purpose - The purpose of this paper is to test some antecedents that influence Universiti Malaysia Kelantan Staff Performance. Design/methodology/approach – A research model based on questionnaire gleaned from the literature was used to collect data through a purposive sampling technique, whereby only those who are working in Universiti Malaysia Kelantan were targeted. The data collected were analysed using structural equation modelling technique with the use of partial least squares approach. Findings – Results show that two out of three antecedents are significant predictors for influencing Job Performance. This paper provides further evidence on the Assement Questionnaire of Dr Talcott Parsons, Dr.Shamim and other related researchers. Research limitations/implication – First, this study cannot be generalized to all other organizations, as the respodents are confined to local university staffs and education industry. Therefore, the results cannot be generalized to organization in other industries. Second, the study is carried out in a relatively new university with lacking of advanced facilities and only a single organization, which is Universiti Malaysia Kelantan in this case. As such, the research neds to be replicated to examine the robustness of the findings across a wider range of organization and samples. Practical Implication – The findings suggest that Job Performance appears to be influenced by Training and Organization Culture but not Working Environment. In a relatively new university, working environment effect is a little bit lower than those two another. This show that a solid training and organization culture might help in pushing up Job Performance even the another contributing factor, working environment is sub-par in a new workplace with lack of facilities and support. Anyway, it is vital for increases working environment in order to keep track of other far better education institution with full facilities and comfortable workplace if Universiti Malaysia Kelantan is looking to be one of the top local universities. Originality/value – This paper adds to the existing literature of Job Performance in a relatively new organization setting. Although there has been some research on the same issue, but it is more on a well-established organization and mostly not education industry.